Electrochemical Coprecipitation of Zinc and Aluminum in Aqueous Electrolytes for ZnO and AZO Coverage Deposition - Natalia A. Martynova; Viktor N. Svishchev; Leonid S. Lepnev; Shakhnozabonu R. Alieva; Elena G. Chertorylskaya; Mikhail E. Vishnevskiy; Alexey D. Bozhko; Anastasia V. Grigorieva (International Journal of Photoenergy)
The aim of this study is to examine the technological challenge of the electrochemical formation of zinc oxide and Al-doped ZnO films (ZnO:Al, AZO) as transparent conductive oxide coatings with complex architectures for solar cell photoanode materials. A cathodic electrodeposition of AZO was performed using aqueous nitrate electrolytes at 25°C. A significant positive deviation in aluminum percentage in the films was demonstrated by the LAES, EDX, and XPS methods, which originates from aluminum hydroxide sedimentation. The photoluminescent characteristics of the ZnO films reveal low band intensities related to intrinsic defects, while the samples with 1 at.% of aluminum show a strong and wide PL band at 600±80 nm and increase in conductivity.